(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
Parents or guardians frequently do not have the necessary repertoires to promote effective self-study behavior on their children. This program had, as a goal, to carry out and assess an educational program for parents or guardians of children with a history of low school performance. Three guardians participated in the research. They were selected by teachers because their children presented learning difficulties. Measures of pre-test, training and post-test were collected through interviews with the guardians and children. In addition, activities were performed in eight meetings, the parents received a handout with the most relevant information; every two session they passed through an evaluation. The results indicate that the program may have promoted changes in the repertoire of parents/guardians to deal with the studies of children and/or on the daily interaction routine in the family environment, especially for one of the three participants